Relaxin Inhibits Ventricular Arrhythmia and Asystole in Rats With Pulmonary Arterial Hypertension - Martin, Brian; Vanderpool, Rebecca R.; Henry, Brian L.; Palma, Joshua B.; Gabris, Beth; Lai, Yen-Chun; Hu, Jian; Tofovic, Stevan P.; Reddy, Rajiv P.; Mora, Ana L.; Gladwin, Mark T.; Romero, Guillermo; et al. (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary arterial hypertension (PAH) leads to right ventricular cardiomyopathy and cardiac dysfunctions where in the clinical setting, cardiac arrest is the likely cause of death, in 70% of PAH patients. We investigated the cardiac phenotype of PAH hearts and tested the hypothesis that the insulin-like hormone, Relaxin could prevent maladaptive cardiac remodeling and protect against cardiac dysfunctions in a PAH animal model. PAH was induced in rats with sugen (20mg/kg), hypoxia then normoxia (3-weeks/each); relaxin (RLX=0, 30 or 400 µg/kg/day, n≥6/group) was delivered subcutaneously (6-weeks) with implanted osmotic mini-pumps. Right ventricle (RV) hemodynamics and Doppler-flow measurements were followed by cardiac isolation, optical mapping, and arrhythmia phenotype. Sugen-hypoxia (SuHx) treated rats developed PAH characterized by higher RV systolic pressures (50±19 vs. 22±5 mmHg), hypertrophy, reduced stroke volume, ventricular fibrillation (VF) (n=6/11) and bradycardia/arrest (n=5/11); both cardiac phenotypes were suppressed with dithiothreitol (DTT=1mM) (n=0/2/group) or RLX (low or high dose, n=0/6/group). PAH hearts developed increased fibrosis that was reversed by RLX-HD, but not RLX-LD. Relaxin decreased Nrf2 and glutathione transferases but not glutathione-reductase. High-dose RLX improved pulmonary arterial compliance (measured by Doppler flow), suppressed VF even after burst-pacing, n=2/6). Relaxin suppressed VF and asystole through electrical remodeling and by reversing thiol oxidative stress. For the first time, we showed two cardiac phenotypes in PAH animals and their prevention by RLX. Relaxin may modulate maladaptive cardiac remodeling in PAH and protect against arrhythmia and cardiac arrest.